Analysis of cancer stem cells in dog's mammary neoplasias - Gouveia, Gabriela Mayumi [UNESP]; Paiva, Milla Bezerra [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Luvizotto, Maria Cecília Rui [UNESP] (My University, 2013)
Mammary tumors are the most frequent cancers in dogs, representing about 50% of tumors, and have a higher incidence in females of middle aged and elderly. These tumors have been used as a model for breast cancer in women due to several common characteristics such as histological and immunohistochemical similarities. In the last decade, studies based on molecular profiles of breast cancer, made possible the identification of some neoplastic cells with characteristics of stem cells - cancer stem cells (CSC). One of the putative molecules of CSCs is CD44. Recent studies have established a crucial link between the epithelial-mesenchymal transition (EMT) and the acquisition of molecular and functional properties of stem cells. For that reason we analyzed the expression of proteins CD44, Cytokeratins AE1/AE3 and Vimentin, in dogs mammary tumors, to investigate the potencial for CSC markers, and its relation with the EMT using immunohistochemistry in paraffin embedded tissues making use of techniques such as Tissue MicroArrays (TMA). Immunostaining of cytokeratin had no significant difference between benign and malignant tumors (p ≥ 0,05), being more intense in malignant tumors. However vimentina showed higher staining intensity in benign tumors, but with no significant difference (p ≤ 0,05). The expression of CD44 was higher in malignant tumors that have greater proliferative and metastatic potencial, however its relation with EMT was not detected in the analyzed tumors. The techniques applied for the TMAs were efficient and can be used in routine and later researches.
Análise das células tronco tumorais em neoplasias mamárias de cães
Keywords: Cancer stem cells; CD44; Dog; Immunohistochemistry